The level of application of the dimensions of total quality management in accounting academic programs in Jordanian universities from the point of view of the teaching staff and students - Eman Ahmad Al-Hneen (University of Science and Technology, Yemen, 2014)
Abstract This study aimed to identify the dimensions of total quality management in accounting academic programs in Jordanian universities from the point of view of the teaching staff and students. To achieve the aims of the study, 165 questionnaires were distributed to the teaching staff, and 140 were given to the students of accounting. The findings reveal that Jordanian universities apply the dimensions of quality related to the administrative system, and the teaching staff, and they do not adhere to the dimensions of quality related to the resources and facilities available to students, plans and curricula, examinations, evaluation of students, admitted students and follow-up of graduates. The study also found that there is a statistically significant differences between the teachers and students in the application of quality dimensions related to examinations , students evaluation, admitted students, and follow-up of graduates. The researcher concluded with some recommendations including a review of admission processes in the specialty, and allocating the number of students according to the facilities available to universities. Key words: total quality management dimensions, plans and curricula, resources and facilities available to students, exams and assessment of students, and students admitted and follow-up of graduates, the administrative system,teaching staff.